2015
DOI: 10.1007/s11882-015-0576-3
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Mucociliary Clearance in Adenoid Hypertrophy and Otitis Media with Effusion

Abstract: Mucociliary clearance (MCC), which exists in many systems, is the first defensive mechanism of the human body. Nasal MCC has an important role in transporting the secretions of the nasal cavity and paranasal sinuses along with the trapped inhaled pathogens to the nasopharynx. Physiologic or pathologic situations that effect nasal MCC, such as temperature, humidity, nasal obstruction, allergic rhinitis, chronic infections, etc., lead to impaired MCC and related local or circumjacent system disorders. With this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 55 publications
0
5
0
1
Order By: Relevance
“…However, we did not observe any relationship between OME episodes and children who lived with pets. Nasal and nasopharyngeal pathologies may contribute to the formation of OME by affecting the upper airway 19 . Sinusitis, septal curvature, hypertrophy of concha choanal atresia, or stenosis can all affect air passage through the nasopharynx.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not observe any relationship between OME episodes and children who lived with pets. Nasal and nasopharyngeal pathologies may contribute to the formation of OME by affecting the upper airway 19 . Sinusitis, septal curvature, hypertrophy of concha choanal atresia, or stenosis can all affect air passage through the nasopharynx.…”
Section: Discussionmentioning
confidence: 99%
“… 44 On the other hand, inflammatory mediators in the nasal mucosa may also directly spread to the ET, leading to ciliary clearance dysfunction and subsequent ETD. 45 Shi et al successfully constructed an animal model of OME by using OVA systemic sensitization and nasal stimulation method. From the tissue structure, they found that the mucosal tissue changes in the ET and the middle ear near the ET were the most obvious in allergic reactions.…”
Section: Possible Mechanisms Of Allergic Responses In the Occurrence ...mentioning
confidence: 99%
“…Пирогова» Минздрава России, e-mail: radtsig_e@rsmu.ru ставанием в физическом и психомоторном развитии. При наличии вышеуказанной симптоматики и соответствующей эндоскопической/рентгенологической картины определяются показания к хирургическому вмешательству -аденотомии [4,5]. Аденотомия является самой частой операцией на лимфоглоточном кольце Вальдейера-Пирогова у детей, составляя до 84,3% хирургических вмешательств, выполняемых в ЛОР-стационарах [6].…”
Section: © коллектив авторов 2017unclassified